Clinical Utility of Circulating Tumor Cells in Patients With Esophageal Cancer - Li, Yang; Wang, Zhenxing; Fu, Rao; Wang, Shuang; Zhang, Tingting; Tian, Xudong; Yang, Dawei (Frontiers in Oncology, 2022)
Background: As one of the most aggressive gastrointestinal tract cancers, esophageal carcinoma (EC) had the tenth morbidity and sixth mortality rate globally in 2020. This study was conducted to investigate whether circulating tumor cells (CTCs) could be used as diagnostic and prognostic tools for patients with EC. Methods: Peripheral blood samples were collected from 129 patients newly diagnosed with EC, 17 individuals with benign diseases, and 75 healthy donors for CTC analysis using negative enrichment-fluorescence in situ hybridization (NE-FISH) approach. The relationship between CTCs (counts and karyotypes) and clinicopathological features was then investigated. Moreover, overall survival (OS) and progression-free survival (PFS) were analyzed to evaluate the predictive value of CTCs. Results: The detection of CTCs using the NE-FISH approach helped in differentiating patients with EC from benign or healthy controls at a threshold of 2 per 3.2 mL peripheral blood with a sensitivity and specificity of 70.54% and 96.74%, respectively (area under the curve = 0.826, 95% CI 0.770–0.874, P < 0.001). The CTC count was associated with tumor depth (P = 0.012), but there was no correlation with other clinicopathological characteristics. Furthermore, the proportion of CTCs with chromosome 7 triploidy was linked to distant metastasis (P = 0.033) and TNM stage (P = 0.002). The OS was significantly shorter for patients with CTCs ≥ 3 than for those with CTCs < 3. Univariate analysis revealed that sex, vascular invasion, distant metastasis, tumor depth, lymph node metastasis, and TNM stage were the significant prognostic factors for patients with EC. Multivariate analysis demonstrated that distant metastasis (hazard ratio (HR) 3.262, 95% CI 1.671–6.369, P = 0.001 for PFS; HR 3.759, 95% CI 1.867–7.571, P < 0.001 for OS) was a significant prognostic factor for patients with EC. Conclusions: Detection of CTCs using NE-FISH could be helpful in the diagnosis of EC. The proportion of CTCs with chromosome 7 triploidy was related to distant metastasis and TNM stage. Patients with CTCs ≥ 3 had short OS, while distant metastasis was an independent factor indicating a poor prognosis for patients with EC.